The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.3390/toxins10070288
|View full text |Cite
|
Sign up to set email alerts
|

Detection of the Potential Inactivation of Tetrodotoxin by Lactic Acid Bacterial Exopolysaccharide

Abstract: Screening for compounds that can neutralize the toxicity of tetrodotoxin (TTX) or reduce its negative effects is necessary. Our study tested the TTX detoxification capacity of exopolysaccharide (EPS) extracted from lactic acid bacteria. EPS of Leuconostoc mesenteroides N3 isolated from the Vung Tau sea (Vietnam), Lactobacillus plantarum PN05, and Lactobacillus rhamnosus PN04 were used in the study. To more completely evaluate the importance of EPS in detoxification, EPS samples of Leuconostoc mesenteroides N3,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…Using the TLC method, a similar result was obtained by Tu et al. (2018), indicating that EPS produced by L. rhamnosus strain was composed with d ‐glucose. In another study, the HPTLC technique revealed the presence of three different types of sugar, namely, d ‐glucuronic acid, fructose, and galactose, in EPS from L. casei B9‐1 and L. plantarum P35 (Shirzad et al., 2018).…”
Section: Resultssupporting
confidence: 80%
“…Using the TLC method, a similar result was obtained by Tu et al. (2018), indicating that EPS produced by L. rhamnosus strain was composed with d ‐glucose. In another study, the HPTLC technique revealed the presence of three different types of sugar, namely, d ‐glucuronic acid, fructose, and galactose, in EPS from L. casei B9‐1 and L. plantarum P35 (Shirzad et al., 2018).…”
Section: Resultssupporting
confidence: 80%
“…Bacterial surface polysaccharides are considered key macromolecules in determining microbe-host interactions through passive forces, electrostatic interactions, and hydrophobic and steric forces [99,100]. Surface polysaccharide production is widely reported in LAB isolates, in particular among members of the Lactobacillus genus [101,102]. Since polysaccharides display a high diversity among LAB [103], they are thought to be involved in determining relevant strain-specific properties for probiotic action, such as the degree of bacterial adhesion to host cells [104106,60].…”
Section: Discussionmentioning
confidence: 99%
“…EPS was collected from bacterial cultures by using ethanol precipitation method with modification. 26,33,34 Basically, the cell free supernatant of bacterium was mixed with absolute ethanol with the ratio 1:2 at 4°C for 24 hours. After that, the mixture was centrifuged at 12,000 rpm for 30 minutes at 4°C.…”
Section: Eps Extractionmentioning
confidence: 99%
“…The study also characterized EPS because EPS involving the TTX toxicity involvement. 26 By detecting carbohydrate using Phenol-sulfuric acid assay, the concentration of EPS was determined (Figure 6). The standard line had the equation y=0.0108x+0.0466 with R2=0.984 >0.97, which meant this standard curve was reliable and can be used for calculating the concentration of EPS.…”
Section: Eps Detectionmentioning
confidence: 99%
See 1 more Smart Citation